Formalization of problem and justification of the set of principles of construction of the system of restoration of weapons and military equipment - Vоlodymyr Dachkovskyi (Social Development & Security, 2020)
Analysis of wars and armed conflicts in recent years confirms that the success of mechanized, tank, assault and other military formations (units) will depend on the effectiveness of the system of supply of troops (forces).